Does Accounting Information System on Financial Report Transparency: A Literature Review - Uswatun Khasanah (DINASTI RESEARCH, 2022)
The full implementation of the accounting system has begun. The practice is still facing various problems related to information systems, knowledge of accountants so that it has an impact on the transparency of financial reports. This study aims to conduct a literature review on increasing the transparency of financial statements through the application of an accounting information system. Research data was collected through literature review using a narrative review commentary. The research aims to provide education that financial statement transparency is very important, accounting information system as an influencing part. With literature review knowledge related to financial statement transparency will increase.